Analysis for the quality control of lupine seeds - Planchuelo, Ana María; Perissé, Patricia (2024)
Ponencia presentada en XV International Lupin Conference 2019. Developing lupin crop into a modern and sustainable food and feed source = XV Conferencia Internacional de Lupino 2019. Desarrollo del Lupino, una fuente modera y sostenible para la alimentación. Cochabamba, Bolivia, 18 al 21 de marzo de 2019.